National wildfowl counts - Atkinson-Willes, G L (Wildfowl, 1959)
After ten seasons of counting wildfowl intensively the time is ripe for a review of what has been achieved so far and for a forecast of what the future may hold. This paper produces comforting confirmation of one of the earliest precepts, that errors in counts due both to the birds' mobility and to the observers' mistakes cancel out provided that large numbers of counts and observers are involved. It also appears that, at least in the areas investigated, the effects of tide and moon are much less important than supposed.